Fotomontagem digital entre o real e o fictício - Brasil, Samia Natividade (BRASIL, 2022)
This research in arts explore the aspects creative and poetic of digital photomontage as a way to create new worlds, between real and fictional. To this end, a literature review was conducted on the development of photography, from analog to digital photomontage, and the deconstruction of the photographic image as a referent to the real. I also studied surrealist productions in photomontages and their creations of oneiric worlds projected through image editing. Parallel to the theory, I developed a practical research with a series of photographic experimentations, searching on fragmentation and collage, oneiric narratives, which resulted in a poetics of confrontation of the subject's reality with his subliminal desires, projected in water reflection, which reflect and expose oppositions. As theoretical support for the study, I used Sandra Rey's methodology for research in artistic processes.